2012
DOI: 10.1186/1746-6148-8-205
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic markers meet the real world: finding diagnostic signatures of corticosteroid treatment in commercial beef samples

Abstract: BackgroundThe use of growth-promoters in beef cattle, despite the EU ban, remains a frequent practice. The use of transcriptomic markers has already proposed to identify indirect evidence of anabolic hormone treatment. So far, such approach has been tested in experimentally treated animals. Here, for the first time commercial samples were analyzed.ResultsQuantitative determination of Dexamethasone (DEX) residues in the urine collected at the slaughterhouse was performed by Liquid Chromatography-Mass Spectromet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 51 publications
4
13
0
Order By: Relevance
“…Moreover, they do not induce any histological alterations in thymus, differently from DEX treatments 11 . The present study confirmed the usefulness of an integrated approach to the investigation of PDN abuse in beef cattle, as previously reported 12,52 . Concerning indirect biomarkers, blood chemistry analysis and histological techniques have been proposed and adopted as alternative screening methods for the prevention of CSs abuse.…”
Section: Pdn and Its Metabolites Are No Longer Detectable By Lc-ms/mssupporting
confidence: 91%
See 1 more Smart Citation
“…Moreover, they do not induce any histological alterations in thymus, differently from DEX treatments 11 . The present study confirmed the usefulness of an integrated approach to the investigation of PDN abuse in beef cattle, as previously reported 12,52 . Concerning indirect biomarkers, blood chemistry analysis and histological techniques have been proposed and adopted as alternative screening methods for the prevention of CSs abuse.…”
Section: Pdn and Its Metabolites Are No Longer Detectable By Lc-ms/mssupporting
confidence: 91%
“…Concerning indirect biomarkers, blood chemistry analysis and histological techniques have been proposed and adopted as alternative screening methods for the prevention of CSs abuse. Recent studies revealed the feasibility of transcriptome analysis using DNA-microarrays as a screening tool to identify the biological response to different illegal drugs, and could be useful to flank the official methods in detecting the use of anabolic compounds in beef cattle 12,[52][53][54][55] .…”
Section: Pdn and Its Metabolites Are No Longer Detectable By Lc-ms/msmentioning
confidence: 99%
“…The advent of "omics" technologies (genomics, transcriptomics, proteomics, metabolomics) now offers interesting perspectives to discover reliable and quantifiable markers, which however still await for full implementation in routine analysis. Transcriptome analysis using DNA-microarrays has been recently explored as a screening method to reveal the biological effects of different anabolic compounds and thus support the existing tools to combat the use of these substances in beef cattle (Cannizzo et al, 2013;Carraro et al, 2009;De Jager et al, 2011;Pegolo et al, 2012;Rijk et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In the detection of anabolic treatments, some advantages of gene expression profiling with respect to the existing conventional methods have already been discussed (Pegolo et al, 2012). For instance, a trascriptomic approach allowed to identify the effects of GPs administration even when the parental compound or its metabolites were no longer detectable in biological fluids by LC-MS/ MS methods or in absence of histological alterations (Cannizzo et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Transcriptomic markers for indirect detection of such GPs have been discussed either in experimentally treated animals or commercial samples, separately. In the present study, we examined the transcriptomic signature of DEX alone or in combination with CLEN in skeletal muscle of experimentally treated beef cattle; furthermore, we compared them to previously screened commercial samples from a field-monitoring study (Pegolo et al, 2012), as well as to a proteomics data coming from the same animals (Stella et al, 2011).…”
Section: Introductionmentioning
confidence: 99%